Modeling neutralization behavior in Information System Security Policy violation among employees in Immigration Department of Malaysia / Mazlin Hani Hasarudin - Hasarudin, Mazlin Hani (2016)
Security violations seriously occur in government agencies and the incidents trend is increasing every passing day. Even though agency applied Information System Security Policy (ISSP), it comes to surprise that majority of security incidents originated from the employees itself. The main problem identified towards security violations comes from rationalization behavior of the employees when intended to violate ISSP that is best known as neutralization. Neutralization in the presence of general deterrence theory (GDT) may cause high ISSP violation, thus lead to higher internal security incidents in government agencies in Malaysia. Therefore, this study aims to identify the neutralization techniques that have positive relationships with ICT security policy violation, as well as determined the GDT that influenced neutralization techniques. This empirical study conducted in ISMS certified Malaysia public agency, that is Immigration Department of Malaysia (IMM) to find the association of neutralization techniques and GDT with ISSP violation. Employees with IT and non-IT background across IMM were participated in a survey consists of vignette scenarios and questionnaires based on main IMM systems that is My lMMs; with ICT Security Officer (ICTSO) and Risk Officer (RO) been interviewed. The results of this study proves that employees in IMM did perform neutralization with defense of necessity was the highest technique adopted. Degree of each neutralization techniques adopted differ accordingly with the presence of GDT that were perceived certainty of sanction and moral belief; whilst gender and age proven to be not influencing. Finally, the findings of this study beneficial IMM to understand employees' behaviour, thus IMM could outline better ISSP and awareness programs and encourages employees to be more ethical. This study also may be a platform for further research on behavior in Malaysia culture to be explored in future.